DISINFECTANTS AND CORONAVIRUS DISEASE 2019 (COVID-19) : A MINI REVIEW - Kanakaraju, Devagi; Micky, Vincent; Glass, Beverley D. (Penerbit UMT, 2021)
The 2019 novel corona virus (2019-nCoV), now known as coronavirus disease (COVID-19), is a major public health threat, impacting both health of populations and economies worldwide, since its emergence in a city called Wuhan, China in December 2019. Known to be highly infectious via human-to-human transmission, the virus can cause severe respiratory infections, resulting in mortality. Because of the current lack of effective drugs to treat or a vaccine to prevent COVID-19 or the SARS-CoV-2, which causes it, disinfectant use is encouraged at a personal level and especially in healthcare and residential settings to control the spread of the virus. The current knowledge of available disinfectants commonly used, their active ingredients and effectiveness in combating COVID-19 will be discussed in this mini review.